Bio-reduction of ferrihydrite-montmorillonite-organic matter complexes: Effect of montmorillonite and fate of organic matter. (1st May 2020) - Zeng, Qiang; Huang, Liuqin; Ma, Jingyu; Zhu, Zihua; He, Chen; Shi, Quan; Liu, Wen; Wang, Xi; Xia, Qingyin; Dong, Hailiang
Abstract: Organic matter (OM) is often associated with Fe (hydr)oxides such as ferrihydrite (Fh) in soils and sediments, forming binary Fh-OM complexes. Microbial reduction of Fh results in destabilization of the complexes and mineral/OM transformation. However, little is known about the role of clay minerals in such processes, despite their common co-existence with Fh and OM in natural environments. Here Fh-OM complexes were synthesized in the presence of montmorillonite (SWy-2), forming ternary Fh-(SWy-2)-OM complexes. A metal-reducing bacterium Geobacter sulfurreducens was used to reduce Fh in the complexes under circumneutral pH and anoxic conditions with or without H2 as extra electron donor. Various spectroscopy and mass spectrometry methods were used to monitor the progress of Fh bio-reduction and mineral/OM transformation. Results showed that G. sulfurreducens utilized mineral-bound OM as electron donor and/or carbon source to couple with Fh reduction. Relative to Fh-OM complex, addition of SWy-2 to Fh-OM complex enhanced the bio-reduction extent of Fh by increasing the proportion of bioavailable OM that was weakly bound to SWy-2. However, its effect on the bio-reduction rate was variable. SWy-2 initially decreased the rate, because it spatially separated OM (electron donor) from Fh (electron acceptor). During later incubation, SWy-2 increased the reduction rate by sorbing biogenic Fe 2+ that would otherwise passivate the Fh and cell surfaces. Bio-reduction transformed mineral-bound OM to microbial products (e.g. necromass, extracellular polymeric substances), but organic compounds with aromatic structures, carboxyl groups and large molecular weight were more resistant to desorption and oxidation. The persistence of these compounds against bio-reduction induced transformation is likely due to their stronger binding with minerals and/or lower nominal oxidation states of carbon relative to other compounds. Our results provide new insights into the role of clay minerals in regulating biogeochemical cycling of solid-phase Fe and transformation of mineral-associated OM in anoxic soil environments.